Access to Online Resources A Guide for the Modern Librarian - Botyriute, Kristina (Springer International Publishing : Imprint: Springer, 2018)
This book is published open access under a CC BY 4.0 licence.The book offers a concise guide for librarians, helping them understand the challenges, processes and technologies involved in managing access to online resources. After an introduction the book presents cases of general authentication and authorisation. It helps readers understand web based authentication and provides the fundamentals of IP address recognition in an easy to understand manner. A special chapter is dedicated to Security Assertion Markup Language (SAML), followed by an overview of the key concepts of OpenID Connect. The book concludes with basic troubleshooting guidelines and recommendations for further assistance. Librarians will benefit from this quick and easy read, which demystifies the technologies used, features real-life scenarios, and explains how to competently employ authentication and access management.